The establishment of the administrative judiciary in Georgia - Sturua, Bidzina (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The study concerns the Georgian administrative judiciary, which was shaped under the influence of European patterns. However, unlike in most European countries, Georgia has not established separate administrative courts – judicial control of the administration is exercised by common courts. The structure of these courts is three-tier and includes district (city) courts, courts of appeal and cassation courts, with adjudicating panels specialized in administrative cases. They adjudicate according to the principles set out in the Code of Administrative Procedure of Georgia adopted in 1999, which emphasizes the importance of the lawful rules of administrative court proceedings, such as the principle of impartiality of proceedings and equality before the law, independence and impartiality of the judiciary.